2011
DOI: 10.1007/s12011-011-9146-2
|View full text |Cite
|
Sign up to set email alerts
|

Altered Heavy Metals and Transketolase Found in Autistic Spectrum Disorder

Abstract: Autism and autism spectrum disorder (ASD) are developmental brain disorders with complex, obscure, and multifactorial etiology. Our recent clinical survey of patient records from ASD children under the age of 6 years and their age-matched controls revealed evidence of abnormal markers of thiol metabolism, as well as a significant alteration in deposition of several heavy metal species, particularly arsenic, mercury, copper, and iron in hair samples between the groups. Altered thiol metabolism from heavy metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 33 publications
3
56
1
Order By: Relevance
“…It was hypothesized that children with autism have a decreased detoxification capacity for Hg because of genetic polymorphism(Mutter et al, 2005).Pb level was significantly higher in our patients with autism compared with the control participants. This finding is in agreement with the findings of El-Ansary et al(2011), but was not in agreement with that ofTian et al (2011), who concluded that there were no significant differences in blood Pb levels among children with autism and controls Obrenovich et al (2011). emphasized the importance of chelating agents as preventive measures for autism.…”
supporting
confidence: 69%
“…It was hypothesized that children with autism have a decreased detoxification capacity for Hg because of genetic polymorphism(Mutter et al, 2005).Pb level was significantly higher in our patients with autism compared with the control participants. This finding is in agreement with the findings of El-Ansary et al(2011), but was not in agreement with that ofTian et al (2011), who concluded that there were no significant differences in blood Pb levels among children with autism and controls Obrenovich et al (2011). emphasized the importance of chelating agents as preventive measures for autism.…”
supporting
confidence: 69%
“…Arsenic, a metalloid that can exist in both organic and inorganic forms, has been found to have harmful effects on the human nervous system (ATSDR 2007;USEPA 2002). Similar to results seen in studies of lead and mercury, results from these studies have been inconsistent, with several reporting no association (Adams et al 2006;Fido & Al-Saad 2005;Adams et al 2013;Rahbar et al 2012;Adams et al 2013), others reporting higher levels of arsenic in children with ASD (Obrenovich et al 2011), and another study reporting lower concentrations in children with ASD compared to controls (Kern et al 2007). …”
Section: Lead Mercury and Arsenic And Neurodevelopmentmentioning
confidence: 74%
“…Biomarkers included altered levels of oxidative stress defence systems, including metallothioneins and antioxidant enzymes. 215 Other markers of oxidative stress, associated heavy metal toxicity and/or low detoxification capacity included abnormal markers of thiol metabolism, 216 transsulfuration abnormalities, 30 urinary organic acids, 29 and increased lead and potassium ions, ATPase activity and lipid peroxidation products. 217 …”
Section: Health Promotion and Chronic Disease Prevention In Canadamentioning
confidence: 99%